Estimating the value and distributional effects of free state schooling - Andreou, Sofia N.; Koutsampelas, Christos; Pashardes, Panos (My University, 2014)
The effects of free of charge state education on income distribution are often studied by allocating government education outlays to households, assuming that these outlays equal the benefit which households attach to state schooling. This paper proposes a demand analysis approach to estimating the 'true' value of state education as perceived by consumers, and uses the results to assess the inefficiency of public provision. Empirical analysis based on data from Cyprus suggests that state schooling costs twice the amount households are willing to pay for. The implications of this finding for the equality and anti-poverty effects of state education are illustrated.
Keywords: Consumer demand; Education; Inequality; Poverty